A case of traumatic isolated duodenal perforation due to blunt abdominal trauma - Ansari, Waqar A.; Gadekar, Deepak B.; Ansari, Asif; Ghosh, Ahana; Malgaonkar, Sumit; Swami, Aishwarya (International Surgery Journal, 2021)
Isolated duodenal injury following blunt abdominal trauma is a rare clinical entity and is often unnoticed leading to delay in management thereby increasing morbidity and mortality. We report a case of isolated duodenal perforation following blunt abdominal trauma and highlight the challenges and decision-making dilemmas associated with its management. The present patient had two perforations, one on the anterior and the other on the posterior wall of the duodenum. Complete duodenal mobilization during laparotomy and a decision of performing pyloric exclusion aided momentously in the management.